Can subunit‐specific phenotypes guide surveillance imaging decisions in asymptomatic SDH mutation carriers?. (28th November 2018) - Tufton, Nicola; Sahdev, Anju; Drake, William M.; Akker, Scott A.
Summary: Objective: With the discovery that familial phaeochromocytoma and paraganglioma syndrome can be caused by mutations in each subunit of the succinate dehydrogenase enzyme (SDH), has come the recognition that mutations in the individual subunits have their own distinct natural histories. Increased genetic screening is leading to the identification of increasing numbers of, mostly asymptomatic, gene mutation carriers and the implementation of screening strategies for these individuals. Yet there is, to date, no international consensus regarding screening strategies for asymptomatic carriers. Design: A comprehensive PubMed search from 1/1/2000 to 28/2/2018 was undertaken using multiple search terms and subsequently a manual review of references in identified papers to identify all clinically relevant cases and cohorts. In this review, the accumulated, published experience of phenotype and malignancy risks of individual SDH subunits is analysed. Where possible screening results for asymptomatic SDH mutation carriers have been analysed separately to define the penetrance in asymptomatic carriers (asymptomatic penetrance). Results: The combined data confirms that "asymptomatic penetrance" is highest for SDHD and when there is penetrance, the most likely site to develop a PGL is head and neck ( SDHD ) and extra‐adrenal abdominal ( SDHB ). However, the risk in SDHB carriers of developing HNPGL is also high (35.5%) and a PCC is low (15.1%), and in SDHD carriers there is a high risk of developing a PCC (35.8%) or abdominal PGL (9.4%) and a small, but significant risk at other sympathetic sites. The data suggest that the risk of malignant transformation is the same for both PCC and extra‐adrenal abdominal PGLs (30%‐35%) in SDHB carriers. In SDHD carriers, the risk of malignant transformation was highest in HNPGLs (7.5%) and similar for sympathetic sites (3.8%‐5.2%). Conclusions: Using this data, we suggest surveillance screening of asymptomatic carriers can be tailored to the underlying SDH subunit and review possible surveillance programmes.